Innovation In English Language Learning Model Based Digital Literacy To Construct Young Learners’ Character - Sujarwo, Sujarwo; Asdar, Asdar; Sabillah, Bellona Mardhatillah; Sukmawati, Sukmawati; Akhiruddin, Akhiruddin; Muh. Syata, Wahyu (Universitas Cokroaminoto Palopo, 2023)
Learning English for children is important, apart from making it easier for children to enter a higher level of education, it also accustoms children to face the demands of the times that use English as an international language, children will be able to communicate well. The aim of this study was to innovate English language learning model based digital literacy to construct young learners’ character. The method used quantitative research with the one group pretest-posttest with the total sample 43 students. Based on the results of study show that learning using software in the form of digital literacy-based English learning media to develop the character education of children. The English learning model applied is not only oriented towards pure science which prioritizes students' cognitive abilities, but is also oriented towards psychomotor and affective abilities, namely the construct the character of the children. It can be concluded that using applications like Canva, Sparkol Video Scribe, and Wordwall, students find studying English to be enjoyable, and this is done in an effort to build the characters of the students